Classification and evaluation of sweet spots of marine shale gas reservoir in Ordovician Wulalike Formation on the westen margin of Ordos Basin - Linlin ZHANG; Kongjie WANG; Fengpeng LAI; Wei GUO; Lili MIAO (Shiyou shiyan dizhi, 2024)
Sweet spot evaluation is of great significance for efficient exploration and development of shale gas reservoirs. Taking the shale reservoir in Ordovician Wulalike Formation on the western margin of the Ordos Basin as the research object, eight experiments including rock section analysis, X-ray diffraction, SEM scanning electron microscopy, low-temperature nitrogen adsorption, isothermal adsorption, total organic carbon (TOC) content test, organic matter vitrinite reflectance (Ro) test and triaxial rock mechanics test were carried out in this study. It is found that the rock type in the target area is gray brown mud shale, with the pore size in the ranges of 2-4 nm and 35-61 nm, and intergranular pores, clay mineral interlayer pores and intragranular pores are developed. The TOC content is 1.01%, the average Ro value is 1.75%, and the brittleness index is 47.8%. By analyzing the influence of different factors on the selection and evaluation of shale reservoir sweet spots, it is concluded that the content of siliceous minerals, clay minerals, pore specific surface area, TOC content and Ro value play a decisive role on the adsorption perfor-mance of the reservoir, the pore size and the number of pore types control the reservoir property, the content of brittle minerals and rock mechanics parameters affect the compressibility of the reservoir. According to the two indexes of adsorption property and reservoir property evaluated by geological sweet spots and the compressibility index of engineering sweet spots, the parameter indexes corresponding to different characteristics are finely classified, and a classification and evaluation scheme of geological sweet spots and compressibility sweet spots of the marine shale gas reservoir in Ordovician Wulalike Formation in the Ordos Basin is preliminarily established. The results show that all characteristic para-meters in the target area meet the grade Ⅱ standard. It could be a sweet spot for shale gas development.